Nativist-populism, the internet and the geopolitics of indigenous diaspora. (April 2020) - Harris, Jonathan
Abstract: The increasing influence of nativist-populism across Europe has provoked public and scholarly debate in recent years, to which political geographers are well placed to contribute. This article synthesises recent work on popular geopolitics and the geopolitics of diaspora to analyse the ways that the MAK-Anavad (the Kabyle government-in-exile) positions itself politically through both reactionary nativism and progressive indigenism. The politics of diaspora, indigeneity and nativism share some common discursive traits relating to territory and belonging, though their starting points and political effects are different. This article outlines and explains the ways the MAK-Anavad's discourse articulates with the nativist-populism of the French Right, arguing that this is possible because of its diasporic situation, colonial history, and a common discourse of anti-Islamism. Online social media, an important new field for the study of popular geopolitics, is argued to offer a key political opportunity structure for the MAK-Anavad and to privilege a populist communication style.